Perceived Health Impact and Usage of Public Green Spaces in Brussels' Metropolitan Area During the COVID-19 Epidemic - Noël, Charlotte; Rodriguez-Loureiro, Lucia; Vanroelen, Christophe; Gadeyne, Sylvie (Frontiers in Sustainable Cities, 2021)
To fight the COVID-19 epidemic, many countries implemented containment measures that made physical distancing the norm and imposed restrictions on the use of public space. In countries where access to public green spaces (PGSs) was safeguarded, they were expected to partially counterbalance the negative health outcomes of these containment measures, as they offered a unique opportunity to meet others, to avoid isolation, and to move, play and relax at a safe distance. Research on PGS use and its objective association with health during the COVID-19 epidemic is rather limited and is based on quantitative research methodologies. Such methodologies are useful to detect objective associations between PGS use and health or between COVID-19 and PGS use, but fall short in explaining the observed associations. This qualitative research filled this gap by examining how PGS users perceived the health advantages of PGSs and how the use of PGSs changed during the epidemic in the Brussels-Capital Region, Belgium. In total, 23 individual face-to-face in-depth interviews were conducted in various PGSs. We found that while PGSs were initially perceived as a possible threat to health in the first period of the epidemic, they gradually became associated in users’ minds with both improved physical and mental health. Although the mechanisms behind this association were also present prior to the epidemic, they became more tangible and more universal. We also found that the use of PGSs changed during the epidemic due to measures and restrictions and due to health risk perceptions. We distinguished 5 different health risk perception profiles in relation to COVID-19: the denier, the fatalist, the negotiator, the conformer and the worrier. These different health risk perceptions impacted on the use of and behaviour within PGSs. This research confirms the importance of PGSs during an epidemic and may inspire further research, offer pointers to policymakers for developing and implementing strategies related to the use of PGSs during epidemics, and assist them in providing available and accessible PGSs and in designing attractive, more epidemic-proof PGSs.